The Rise and Effect of Virtual Modalities and Functions on Organizational Leadership: Tracing Conceptual Boundaries Along the E-Management and E-Leadership Continuum - Montgomery VAN WART; Alexandru ROMAN; Sharon PIERCE (Transylvanian Review of Administrative Sciences, 2016)
The massive shift to virtual modalities and functions has changed the context of leadership and organizational structures, and thus how leadership is exercised. To date, the fi elds of e-leadership and e-management, or more generally, virtual leadership, have been unable to make much progress. This exploratory study uses adaptive structuration theory, an approach recommended by Avolio (2001 and 2014), to provide a broad framework that is modifi ed for the fi eld. It uses the multi-method, multi-level approach recommended by structuration theory. Findings regarding three specifi c advanced information technologies (AITs) are discussed, study limitations are provided, and future research opportunities are reviewed.